1982
DOI: 10.1128/mcb.2.7.853
|View full text |Cite
|
Sign up to set email alerts
|

DNA content, kinetic complexity, and the ploidy question in Candida albicans.

Abstract: Candida albicans is a dimorphic fungus that is pathogenic for humans. No sexual cycle has been reported for this fungus, and earlier reports have differed on whether typical strains of C. albicans are haploid or diploid. Previous estimates of the DNA content of C. albicans varied by one order of magnitude. We used three independent methods to measure the kinetic complexity of the single-copy DNA from a typical strain of C. albicans (strain H317) to determine the DNA content per haploid genote; we obtained valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(85 citation statements)
references
References 40 publications
5
79
0
1
Order By: Relevance
“…The array described here was able to detect genomic DNA at levels of 1 to 10 pg per assay by testing serial 10-fold dilutions of fungal DNA (data not shown). If the DNA content of a fungal cell was equivalent to 37 fg as a yeast cell (39), then the detection limit of the array was equivalent to 27 to 270 cells per assay.…”
Section: Identification Of Dermatophytes By the Arraymentioning
confidence: 99%
“…The array described here was able to detect genomic DNA at levels of 1 to 10 pg per assay by testing serial 10-fold dilutions of fungal DNA (data not shown). If the DNA content of a fungal cell was equivalent to 37 fg as a yeast cell (39), then the detection limit of the array was equivalent to 27 to 270 cells per assay.…”
Section: Identification Of Dermatophytes By the Arraymentioning
confidence: 99%
“…However, a deeper understanding of the biology and pathogenicity of C. albicans has been hampered by the difficulties in carrying out genetic analysis in this species. It has been suggested that most of the currently isolated C. albicans strains are diploid (Olaiya & Sogin, 1979 ;Riggsby et al, 1982) and, although contested (Sarachek, 1983), this is now widely accepted. Mitotic recombination, induced by mild UV treatment, has been used to follow the segregation of many alleles, through the formation of sectored colonies, and has provided a means for the genetic characterization of many mutants and variants (Whelan et al, 1980;Whelan & Magee, 1981 ;Whelan & Soll, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The average fluorescence intensity of the stationary phase cells of Saccharomyces cerevisiae haploid strain, X2180-1A, was used as a standard value and the fluorescence value was adjusted to 18, as the haploid DNA content of this organism is reported to be 18 fg (17).…”
Section: Resultsmentioning
confidence: 99%